Numerical modeling of a prototype cardiac assist device by implementing fluid-structure interaction - Shahrokh Rahmani; Mehrnaz Oveysi; Alireza Heidari; Mahdi Navidbakhsh; Mansour Alizadeh (Artery Research, 2018)
The purpose of this study is to simulate the blood flow in a 2D axisymmetric model for the aorta assisted with a type of cardiac assist device in which the balloon part is surrounding the ascending aorta and can pump the blood flow by its inflation/deflation. The blood flow and von Mises stress in the assisted aorta are investigated by fluid–structure interaction analysis (FSI). Taking into consideration three materials and seven thicknesses for the balloon in one layered and three-layered aorta models, the influences of each of these states on the mentioned parameters have been studied. The numerical simulation demonstrates that by using this cardiac assist device, the maximum blood flow velocity increases up to 92% at the time of maximum pressure on the balloon and this configuration augments the maximum von Mises stress. The magnitude of the maximum von Mises stress and the maximum blood velocity reduce by thickening the balloon from 0.8 mm to 2 mm up to 8.9% and 9.95%, respectively. The maximum pressure at the outlet of the aorta increases from 9.77 kPa to 10.4 kPa at the time of applying maximum pressure on the balloon. With the one-layered aorta model, the maximum von Mises stress occurs at the innermost layer of the aorta’s wall on each line across the wall and the balloon. Using the three-layered aorta model, the location of the maximum stress is shifted to the juncture of intima and media layers.